2020
DOI: 10.1128/msystems.00358-20
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Viral Satellites Manipulates Invading Virus Gene Expression and Can Affect Cholera Toxin Mobilization

Abstract: Many viruses possess temporally unfolding gene expression patterns aimed at subverting host defenses, commandeering host metabolism, and ultimately producing a large number of progeny virions. High-throughput omics tools, such as RNA sequencing (RNA-seq), have dramatically enhanced the resolution of expression patterns during infection. Less studied have been viral satellites, mobile genomes that parasitize viruses. By performing RNA-seq on infection time courses, we have obtained the first time-resolved trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 78 publications
11
62
0
Order By: Relevance
“…Western blot analysis of total protein from PLE(−) and PLE(+) hosts over the course of infection demonstrated detectable capsid protein by 12 minutes post-infection and confirmed that PLE(+) infections produce approximately one-third as much ICP1 capsid protein as PLE(−) infections at all timepoints where capsid protein was detected (Figure 1D, Supplementary Figure S3A). These results together with the capsid operon reporter phage validate the observation of capsid operon transcriptional repression mediated by PLE (21) and confirm that this transcriptional repression results in a reduction in total ICP1 capsid monomer production during the late stages of a PLE(+) infection.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Western blot analysis of total protein from PLE(−) and PLE(+) hosts over the course of infection demonstrated detectable capsid protein by 12 minutes post-infection and confirmed that PLE(+) infections produce approximately one-third as much ICP1 capsid protein as PLE(−) infections at all timepoints where capsid protein was detected (Figure 1D, Supplementary Figure S3A). These results together with the capsid operon reporter phage validate the observation of capsid operon transcriptional repression mediated by PLE (21) and confirm that this transcriptional repression results in a reduction in total ICP1 capsid monomer production during the late stages of a PLE(+) infection.…”
Section: Resultssupporting
confidence: 81%
“…This requirement was dictated by the unique challenges presented by the lifecycle of ICP1 within a V. cholerae host cell, which is rapid and highly destructive: infections produce ~90 viable phage progeny per infected cell in under 20 minutes (15). The bacterial host chromosome is rapidly degraded (26) and transcriptional profiling during infection did not reveal any ICP1, PLE, or V. cholerae genes with consistent transcriptional activity over the infection time-course (21). This limits feasibility of evaluating the targeted repression of the capsid operon by RT-qPCR, which would require a proper normalization control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further similarities are that the excised PLE overreplicates its helper phage, outperforms the phage genome in packaging and consequently, highly reduces the spread of the helper phage ( 59 ). Thereby PLEs provide efficient defence for their host against its lytic phage invaders and ensure their own horizontal transfer at the expense of the helper phage ( 59 , 60 ). PLE also has its own replication origin and encodes a RepA resembling Gram+ plasmid replication initiation factors.…”
Section: Discussionmentioning
confidence: 99%